Early Closure of End Ileostomy Following Visceral Slide Assessment Using Abdominal Ultrasound - Jang, Myong Chol; Ri, Hye Song; Kang, Hui Chol (Medical Science Journal for Advance Research, 2025)
Purpose: The purpose of our study is to decide whether to perform or not early closure of end ileostomy based on the release of abdominal adhesion following visceral slide assessment using ultrasound after its creation. Method: 59 patients with stoma closure from January 2022 to May 2024 were involved in the study. Of these, 9 patients were excluded from the analysis since stoma became permanent, 50 patients (20 female patients) were included. They were divided into 2 groups. In EC(early closure) group, we decided operation timing using ultrasound and performed closure within 180 days after ileostomy. In LC(late closure) group, we performed closure after 180 days based on doctor’s judgment without former procedure. Result: There was no significant difference in the number of adhesions separated by operation between the 2 groups. Stoma-related complications and readmission rate in EC group were significantly lower than in LC group. No significant difference was noted in terms of operative time, length of postoperative hospital stay, operative intestine injury, morbidity and mortality between the 2 groups. Conclusion: Our findings suggest that stoma closure within six months performed in the certain period based on the ultrasound assessment can achieve a safety level equal to that of stoma closure after six months.